(untitled) (Andamios, Revista de Investigación Social, 2010)
In the last two decades, agricultural productivity growth has been remarkable despite the weakening of the public policies which promote it. A reason that made this growth possible was the strengthening of productive chains and contract agriculture, creating a new model that focused on the most productive farming regions and in the most efficient businesses that were capable of increasing productivity in order to counter the effects of increasing input costs and decreasing prices. It’s a polarizing model that excludes any kind of production units that cannot compete on the market and also encourages concentration of agricultural production. From 1992 to 2004, 1.4 million farm households of all sizes disappeared, contrary to the popular economic theory at the time, which essentially condemned the poorest. To survive the constant fall in farm prices, “campesino” production units diversify their sources of income and increase their rate of employment but are still unable to overcome poverty.